Voltammetric Determination of Amoxicillin Using a Reduced Graphite Oxide Nanosheet Electrode - Thi Hai Yen Pham; Thi Trang Mai; Hoang Anh Nguyen; Thi Thu Hien Chu; Thi Thu Ha Vu; Quoc Hung Le (Journal of Analytical Methods in Chemistry)
A reduced graphite oxide nanosheet electrode (RGOnS) was prepared as a sensor for amoxicillin (AMX) detection, an antibiotic commonly used in the livestock farm, by the square-wave adsorptive stripping voltammetry technique. Graphite oxide with nanosheet shape was produced from a graphite electrode by a chronoamperometry process at 5 V and then an electrochemical reduction process was carried out to form RGOnS with restored long-range conjugated networks and better conductivity. The electrodes were characterized by SEM, EDX, and FTIR spectroscopy. The RGOnS electrode prepared at an optimal reduction potential of −1 V for 120 s exhibits a larger electrochemical active surface area, and the obtained oxidation signal of AMX is approximately ten times higher than that of the pristine graphite electrode. The analytical conditions such as the pH of electrolyte and accumulation time were optimized. The calibration curve built under the optimal conditions provided a good linear relationship in the range of AMX concentration from 0.5–80 µM with the correlation coefficient of 0.9992. The limit of detection was calculated as 0.193 µM. Satisfactory results are obtained from the detection of the AMX in different samples using the prepared electrode.